Evaluación de los diferentes niveles de fertilización con NPK en el cultivo de maíz (Zea mays) sembrado en condiciones de secano en la zona de Ventanas. - Aguilar Litardo, José Fabián (2019)
The application of fertilizers is an indispensable activity in the corn production process, due to the demand for nutrients is high and the soil affected to present nutritional unevenness preventing in this way that the plants have a provision the necessary requirements for their development limiting compliance with the physiological functions required resulting in poor harvests and lower economic income. The present Research Project had as a general objective to evaluate the effects of the different levels of fertilization with NPK, in the corn crop (Zea mays) planted under rainfed conditions in the Ventanas area in order to assess the response of the crop to NPK applications, where we proceeded to evaluate the parameters of development and productivity were evaluated by adding fertilizers among which Urea, DAP and Potassium Muriate were used, establishing different levels of fertilization that corresponded to different doses of nitrogen, phosphorus and potassium, including a treatment to which no any type of fertilizer was added. The randomized complete block design was used and to obtain differences between the averages obtained, the Tukey test was applied at a 95% probability. Variables such as plant height at 15, 30 and 60 days, ear insertion height, male and female flowering days, leaf area index, number of plants and ears harvested, weight of 1000 grains were evaluated and yield in kg ha-1. It should be noted that the addition of fertilizers resulted in obtaining larger plants in all evaluation periods by registering 251.00 cm plants at 60 days of evaluation and presenting 16.72 cm and 188.67 g cobs of the ear weight in those treatments where a complete fertilization was applied, in addition to achieving the best performance by applying 160 N, 60 P and 90 K with 10392.23 kg ha-1 thus obtaining the best Benefit/Cost ratio with 1.96 and profitability of 96.48%. Keywords: fertilization, corn, NPK.